2009
DOI: 10.11606/issn.2317-0190.v16i4a103273
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de úlcera por pressão em indivíduos com lesão de medula espinhal e a relação com a capacidade funcional pós-trauma

Abstract: O estudo observacional, transversal, teve por objetivos caracterizar indivíduos adultos que sofreram Lesão de Medula Espinhal (LME) entre janeiro de 2003 a Julho 2006 em hospitais credenciados ao SUS no município de Ribeirão Preto, avaliar a capacidade funcional utilizando a escala Medida de Independência Funcional (MIF), considerando o nível de lesão e identificar a prevalência de úlcera por pressão (UP). Após a aprovação do Comitê de Ética em Pesquisa o estudo foi realizado, mediante consentimento dos partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…From the understanding of the etiologic factors of PIs and their prevalence in the wheelchair user population, it can be inferred that they are a major concern in terms of health and quality of life of people with reduced mobility and/or wheelchair users, leading them to have their daily life surrounded by the resulting limitations. Rabeh et al (2009) corroborate emphasizing the frequency of the development of PIs, which interferes in physical, psychological and social conditions, causing negative impact in quality of life.…”
Section: Introductionsupporting
confidence: 56%
“…From the understanding of the etiologic factors of PIs and their prevalence in the wheelchair user population, it can be inferred that they are a major concern in terms of health and quality of life of people with reduced mobility and/or wheelchair users, leading them to have their daily life surrounded by the resulting limitations. Rabeh et al (2009) corroborate emphasizing the frequency of the development of PIs, which interferes in physical, psychological and social conditions, causing negative impact in quality of life.…”
Section: Introductionsupporting
confidence: 56%
“…It is important to highlight the alarming data on the high number of people with income from retirement/benefits or unemployed. Current studies have also found the prevalence of SCI in the economically active population, thus impacting the low contribution to GDP and the use of greater financial resources from public services for health care and social security (Brazil, 2015b;Rabeh, Caliri, & Hass, 2009;Faleiros et al, 2020). These results underscore the government's importance of investing in public policies focused on rehabilitation, better accessibility and opportunities to return to the job market and awareness campaigns for safe driving and the prevention of urban violence.…”
Section: Discussionmentioning
confidence: 99%
“…According to worldwide epidemiological data, 15 to 40 individuals suffer TSCI per million people. In the U.S., 12,000 new cases of TSCI are recorded per year, while in Brazil this number is between 6000 and 8000, of which 80% are male, and 60% are between 10 and 30 years of age [2] and young adult males between the ages of 18 and 40 who are fully employed and contribute to the country's gross domestic product (GDP) [3].…”
Section: Introductionmentioning
confidence: 99%
“…The main causes of TSCI are motor accidents, gunshot and knife wounds, falls, sports, work accidents, and diving into shallow water [2]. Most patients are young males and most of these cases lead to complications, especially involving fecal incontinence, sexual dysfunction, and reduced or absent sensory reflexes that negatively affect quality of life (QOL), way of life, and the capacity to live a healthy lifestyle [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%